The Effectiveness of the Guided Discovery Learning Model Assisted by PhET Virtual Laboratory Simulations on Students’ Physics Learning Outcomes - Indah Maryani; Supratman; Aulia Mursida; Akmal Nadya (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
One of the challenges in physics education is the low level of conceptual understanding due to teaching methods that do not actively engage students. This study examines the effectiveness of the Guided Discovery learning model, assisted by PhET Simulation, in improving physics learning outcomes related to sound waves for grade XI MIPA students at SMAN 10 Mataram. A quasi-experimental method with a Static Group Pretest-Posttest Design was employed. Purposive sampling was used to select experimental and control groups. Data were collected through a 30-item multiple-choice test and analyzed using mean scores, normalized gain (N-Gain), normality and homogeneity tests, and an independent t-test. The results showed a significant improvement in the experimental class with an N-Gain of 0.49 (moderate), compared to 0.35 (mild) in the control class. The indicators of understanding and applying showed high gains. The independent t-test confirmed a significant difference (p < 0.05) between the groups. In conclusion, the Guided Discovery model supported by PhET Simulation effectively enhances physics learning outcomes. This study suggests integrating interactive technology-based learning to improve the quality of science education.